The playing characteristics of American trombones and German-system bassoons - Galloway, David John (Rhodes University, Faculty of Humanities, Department of Music, 1985)
Preface: South Africa, a country renowned for its mineral wealth has, perhaps manufacturing paradoxically, no musical wind instrument industry of its own as yet. Thus performers, educators and students alike have either to travel to Europe or America to select an instrument, or to import an expensive instrument that may be both unseen and untried, as very few musical instrument dealers are prepared to outlay capital on stock which appeals to a decided minority of their potential customers. Alternately, a purchase of a particular make or model can be made on the basis of a hearsay opinion; at best, the opportunity for first-hand assessment is minimal. It is the trombone of U. S.A. manufacture and the German bassoon which represent the current state of their respective manufacturing arts, and the yardsticks by which their many imitator's efforts are measured. One of the main aims of this Thesis is to describe in objective terms what has been experienced subjectively over the years of involvement with these instruments -- arguably a task similar to that of the art critic, but operating within more positively defined parameters namely, what works for the student and professional. , and what doesn't. The candidate claims credit for introducing the large-bore Bb/F trombone to South Africa in 1961, following with the introduction of the Â·first double-valve bass trombone in 1965, and the first in 1979. The first Schreiber bassoons The advantages and trombone and other bassoon and other such instrument with in-line rotors of the new 5000 series larger-bore was likewise introduced in 1981. pitfalls of " doubling" between the wind instruments , and between the winds, are disc ussed at length in the final section of the Thesis.
Keywords: Trombone Bassoon